Heat transfer process during filtration drying of match splints - Kuzminchuk, Tetiana; Atamanyuk, Volodymyr (Видавництво Львівської політехніки, 2025)
The study proposes filtration drying for drying match splints. Experimental methods for investigating heat exchange between the heat agent and the material are presented. Theoretical aspects of heat transfer during filtration drying are analyzed. The effect of the heat agent's velocity on heat exchange efficiency is determined within the Reynolds number range of 200 ≤ Re ≤ 500. The experimentally obtained data are generalized using a dimensionless complex. A dependency for determining the heat transfer coefficient is proposed. A correlation between theoretical and experimental values of the heat transfer coefficient is provided.
Keywords: filtration drying; match splints; external heat transfer; heat transfer coefficient; stationary layer